Karakteristik Pasien Penyakit Parkinson: Studi Deskriptif Longitudinal di Rumah Sakit Rujukan Provinsi Maluku - Supiyat Putri, Dziqrina khairunnisya; Huwae, Laura Bianca S.; Devi, Cokorda Istri Arintha; Bension, Johan Bruiyf (Alami Journal (Alauddin Islamic Medical) Journal, 2025)
Parkinson's disease is a progressive neurodegenerative disorder with rapidly increasing global prevalence and disability rates, and it is projected to become the second leading cause of death by 2040. This study is a quantitative descriptive study with a cross-sectional design, utilizing secondary data obtained from the medical records of Parkinson’s patients at Dr. M. Haulussy General Hospital Ambon from 2018 to 2022. The study involved 56 Parkinson’s disease patients, with the majority aged 61–70 years (28 patients, 50.0%), predominantly male (33 patients, 58.9%), and mostly retirees (24 patients, 42.9%). A total of 33 patients (58.9%) had a smoking habit, 45 patients (54.9%) had comorbid hypertension, and the most common treatment was a combination of levodopa and pramipexole, used by 21 patients (23.2%). These findings are expected to provide an overview of the characteristics of Parkinson’s patients and serve as a basis for policymaking efforts aimed at prevention, early detection, and more effective management of Parkinson’s disease in the local area.